2012
DOI: 10.1002/jat.2712
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity on human cells of Cry1Ab and Cry1Ac Bt insecticidal toxins alone or with a glyphosate‐based herbicide

Abstract: The study of combined effects of pesticides represents a challenge for toxicology. In the case of the new growing generation of genetically modified (GM) plants with stacked traits, glyphosate-based herbicides (like Roundup) residues are present in the Roundup-tolerant edible plants (especially corns) and mixed with modified Bt insecticidal toxins that are produced by the GM plants themselves. The potential side effects of these combined pesticides on human cells are investigated in this work. Here we have tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 26 publications
1
39
0
1
Order By: Relevance
“…Routine blood biochemical indexes, such as glucose and cholesterol, represent only a very small part of the serum metabolome. In contrast, serum metabolome profiling is able to provide a wealth of biochemical data, therefore very useful in medical practice and safety assessment (Lindon et al, 2004;Nishiumi et al, 2010). In the present study, 446 metabolites were identified from the monkey serum samples, and the serum metabolomic profiles from normal control diet, 60% non-GM diet and 60% GM diet groups were subjected to PCA.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Routine blood biochemical indexes, such as glucose and cholesterol, represent only a very small part of the serum metabolome. In contrast, serum metabolome profiling is able to provide a wealth of biochemical data, therefore very useful in medical practice and safety assessment (Lindon et al, 2004;Nishiumi et al, 2010). In the present study, 446 metabolites were identified from the monkey serum samples, and the serum metabolomic profiles from normal control diet, 60% non-GM diet and 60% GM diet groups were subjected to PCA.…”
Section: Discussionmentioning
confidence: 98%
“…For example, Fares and El-Sayed (1998) reported that CryI potato diet feeding caused fine structural changes in the ileum of mice. In addition, Mesnage et al (2013) reported that Cry1Ab and Cry1Ac had cytotoxic effect on human cells.…”
Section: Introductionmentioning
confidence: 97%
“…Given the frequency of spray applications using glyphosate, nasal inhalation exposure to the spray is extremely likely to occur. While there are no current reports regarding potential glyphosate toxicities following nasal inhalation, studies in cell culture (Slaninova et al, 2009;Koller et al, 2012;Mesnage et al, 2013;Prevot-D'Alvise et al, 2013) have suggested potential toxicities to several human cell types, including those obtained from the buccal, nasal, and lower gastrointestinal tract, and other investigations have demonstrated toxicity to the olfactory systems of several species of fish (Slaninova et al, 2009;Solomon et al, 2013). Although glyphosate itself has been shown to be extremely safe in humans following dermal exposure, toxicities from commercial products have been reported to be induced by the excipients contained in the products, especially the surfactants used to improve the permeability of glyphosate across plant cell walls (Gasnier et al, 2009;Allen and Levy, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…The effects were observed with relatively high concentrations of the toxins; however, further investigations should be conducted to find out how such toxins impact the cells. In addition, it should be taken into account if there are combination effects with other compounds in the food (Mesnage et al 2011). By introducing the toxin-gene into the plant, the structure of the toxin is modified and may cause its selectivity to be changed.…”
Section: World Controversymentioning
confidence: 99%